(untitled) (CAHIERS MAGELLANES-NS, 2024)
Gastrointestinal bleeding is a life-threatening medical emergency that can be a cause of morbidity and mortality. In the case of gastrointestinal bleeding, the first choice for diagnosis is endoscopy. However upper endoscopy has the limitation of detecting the source of bleeding in the small intestine due to various etiologies. Therefore, contrast-enhanced computed tomography (CECT) can be performed as the first choice. However, it can be difficult for the conventional CT scanner to identify active gastrointestinal bleeding and differentiate between two materials having the same or very similar CT numbers. In addition, non-enhanced and several contrast-enhanced images are needed as multiple-phase scans to identify and diagnose gastrointestinal bleeding. This issue can be overcome by using dual-energy CT, which can acquire the changes in attenuation measurement by using two different spectra. As a result, it can be easy to differentiate between two material compositions. Additionally, it offers a variety of post-processing applications like iodine mapping, virtual non-contrast (VNC) imaging, and low-energy monochromatic images. The purpose of this article is to describe the basic principles of dual-energy CT with post-processing applications and its modified scanning protocol in comparison with conventional CT scans, which can significantly reduce patient dose. It will also discuss the potential advantages of dual-energy CT in comparison with the various recommended imaging modalities in order to diagnose GI bleeding.